Do U.S. Firms Hold More Cash than Foreign Firms Do? - Pinkowitz, Lee; Stulz, René M.; Williamson, Rohan (Review of Financial Studies, 2016)
From 1998 to 2011, U.S. firms held more cash on average (but not at the median) than similar foreign firms (foreign twins) did. The average difference in cash holdings does not increase after 2008, and it is driven by highly R&D-intensive U.S. firms. Because there are almost no similarly R&D-intensive foreign firms, mean comparisons involving these U.S. firms are not reliable. Without these U.S. firms, neither U.S. multinational firms nor purely domestic U.S. firms hold more cash than their foreign twins do. Country characteristics have negligible explanatory power for differences in cash holdings between U.S. firms and their foreign twins. Received April 17, 2014; accepted August 4, 2015 by Editor David Denis.